Fertility Behavior of Turkish Migrant Men in Europe Compared to Stayers at Origin - Nadja Milewski; Helen Baykara-Krumme (Journal of International Migration and Integration, 2021)
This paper addresses the fertility behavior of Turkish men in Europe from a context of origin perspective. Men of the first and subsequent migrant generations are compared with "stayers" from the same regions of origin in Turkey. We pay special attention to the men's reasons for migration by distinguishing between work and nonwork motivations for migration. We use data from the 2000 Families Study, which was conducted in 2010 and 2011 in Turkey and in western European countries; the sample consists of about 3,500 men. We analyze the transitions to fatherhood as well as to second and third births using event-history analyses; and we investigate the cumulated number of children using Poisson regression analysis. As the men were aged 18–92 at the data collection, we carry out separate models for birth cohort groups. Our findings provide support for the hypothesis of the interrelatedness of events. First-generation migrant men show elevated first birth transitions, which are closely linked to marriage and migration. However, in contrast to the pattern that is often found for women, this effect is observed for labor as well as for nonwork migrants. The rates of transition to a second and a third birth differ less from those of stayers. Analyses of cumulated fertility at age 41 or older further suggest that the migrants' overall numbers of children are smaller than those of the stayers in Turkey. Thus, our findings indicate that there are dissimilation processes and crossover trends among emigrant men characterized by higher rates of transition to family formation linked to migration but lower overall fertility.
Keywords: 300; Male fertility; Birth transitions; Turkish migrants; Turkey; Dissimilation perspective